2004
DOI: 10.1210/jc.2003-031410
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Resistin Concentrations and Insulin Resistance in Nonobese, Obese, and Obese Diabetic Subjects

Abstract: Early reports suggested that resistin is associated with obesity and insulin resistance in rodents. However, subsequent studies have not supported these findings. To our knowledge, the present study is the first assessment in human subjects of serum resistin and insulin sensitivity by the insulin clamp technique. Thirty-eight nonobese subjects [age, 23 +/- 4 yr; body mass index (BMI), 25.4 +/- 4.3 kg/m(2)], 12 obese subjects (age, 54 +/- 8 yr; BMI, 33.0 +/- 2.5 kg/m(2)), and 22 obese subjects with type 2 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
197
4
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(229 citation statements)
references
References 27 publications
17
197
4
11
Order By: Relevance
“…6,13,16 Besides sexual dimorphism of body fat distribution differences in the sex steroids are discussed to be responsible for the observed differences. 12,15,27,28 However, resistin concentrations have been reported to be independent of menstruation cycle and sex hormones in adult women 7 and resistin levels did not significantly differ between prepubertal and pubertal boys.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…6,13,16 Besides sexual dimorphism of body fat distribution differences in the sex steroids are discussed to be responsible for the observed differences. 12,15,27,28 However, resistin concentrations have been reported to be independent of menstruation cycle and sex hormones in adult women 7 and resistin levels did not significantly differ between prepubertal and pubertal boys.…”
Section: Discussionmentioning
confidence: 93%
“…2,3 Studies in humans are even more controversial. 4,5 In crosssectional studies in adulthood, serum resistin was reported to be related to fat mass [6][7][8] and to insulin resistance, [9][10][11][12] while other reports reveal no correlations to BMI, percent body fat 11,[13][14][15] or to insulin sensitivity. 13,14,16,17 Longitudinal data are necessary to analyze the relationships between resistin, obesity, and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite the species differences, survivors of myocardial infarction displayed elevated levels of resistin [8] and increased plasma resistin level was observed in the serum of obese [8] and type 2 diabetic patients [9]. TZD treatment resulted in decreased plasma resistin levels in patients with type 2 diabetes [10], suggesting resistin plays an important role in the etiology of insulin resistance and diabetes; however, others have failed to show this association [11], [12]. Recently, resistin was shown to impair glucose transport in isolated cardiomyocytes [13] and to be up-regulated by cyclic stretch and aorta-caval shut [14], suggesting resistin may affect cardiac function in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite the species differences outlined above, an increased plasma resistin concentration was observed in the serum of obese [16] or type 2 diabetics [17] and thiazolidinedione treatment resulted in decreased plasma resistin levels in patients with type 2 diabetes [18]. Furthermore, although some studies suggest a link between resistin and insulin sensitivity [19] others have failed to show an association with insulin resistance [16,20,21]. Similarly, genetic analyses have suggested that resistin plays a role in the aetiology of insulin resistance and diabetes [22,23], whereas others contest this view [24].…”
Section: Introductionmentioning
confidence: 99%